Makerspace Implementation and Pandemic Response - Timothy Hurley (Issues in Science and Technology Librarianship)
Makerspaces have continued to be a popular addition to the services offered by libraries. This article will address the creation and implementation of one at a mid-sized medical library. The writer will summarize their personal experience of the steps taken towards opening the makerspace and give insight into the process. This article will also address the trying times brought on by Covid-19 and the challenges faced in an operational perspective.